The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s10484-022-09571-1
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Patients’ Age-Related Benefits from Mobile Neurofeedback-Therapy in Quality of Life and Self-efficacy: A Clinical Waitlist Control Study

Abstract: Electroencephalographic neurofeedback (EEG NF) can improve quality of life (QoL) and reduce distress by modifying the amplitude of selected brain frequencies. This study aims to investigate the effects of NF therapy on QoL and self-efficacy in cancer patients and to explore age-related reactions. In a waitlist control paradigm, psychometric data (EORTC QLQ-C30, General Self-Efficacy Scale) of 20 patients were collected at three different time points, each five weeks apart. An outpatient 10-session NF intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Further analysis showed that this effect was stable only for the NF therapy. In accordance with Schmidt et al 10 evidence for age effects was found. Interestingly, no significant increase in QoL was achieved through the mindfulness control.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Further analysis showed that this effect was stable only for the NF therapy. In accordance with Schmidt et al 10 evidence for age effects was found. Interestingly, no significant increase in QoL was achieved through the mindfulness control.…”
Section: Discussionsupporting
confidence: 89%
“…The length and duration of the NF was based on the few already existing findings 8 on NF interventions in cancer patients ranging from 10 to 100 sessions twice a week. In this study each session had the following structure: (9)(10)(11)(12)(13) and theta/beta (>20 Hz) reduction for 10 minutes.…”
Section: Neurofeedback Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…We expect a moderate effect size of partial η 2 p =0.06, and a mean correlation between within-subject measures of r=0.3, which results in a required sample size of n=27 42. Based on a previous study of our study group on NFB treatment in the outpatient setting, we expect a dropout rate of 13% 43. Therefore, we will include 31 participants in the study.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Overall, current literature suggests a benefit of BFB and/or NFB in patients with various psychosomatic illnesses. However, while BFB has already been heavily researched in the outpatient setting (18)(19)(20)(21), the usage of BFB and/or NFB in an inpatient setting for mental health disorders has been rarely investigated. To our knowledge, only one study examined the usage of BFB in inpatients with eating disorders (22).…”
Section: Introductionmentioning
confidence: 99%